A new species of Epidryos (Rapateaceae) from Guyana - Rodrigues, Rodrigo Schütz; Flores, Andréia Silva (Phytotaxa, 2017)
Epidryos matheusii, a new species of Rapateaceae endemic to Guyana, is described and illustrated. The new species differs from its congeners in having the base of leaf blades gradually passing into a petiole 8–12 cm long and the smallest bracteoles and sepals. An updated key to all known species of Epidryos is provided.